2010
DOI: 10.1128/jcm.01617-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flocked and Rayon Swabs for Detection of Nasal Carriage of Staphylococcus aureus among Pathology Staff Members

Abstract: Comparison of flocked swabs (E-swabs; Copan) to the standard rayon swabs (Copan) was undertaken for detection of Staphylococcus aureus nasal carriage among staff at Dorevitch Pathology in Heidelberg, Melbourne, Australia. Among 100 volunteers, 36 were found to be colonized with S. aureus by one or both swab results. The prevalence detected by E-swabs was 35%, and the prevalence through rayon swabs was 34% (95% confidence interval [CI] for the difference in proportions, ؊12 to 14). Thirty-three volunteers teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…Similarly, Van Horn et al have demonstrated that nylon flocked swabs placed in Amies liquid medium yielded greater organism release (18). In contrast to these results, a recent study from De Silva et al (8) did not find any difference in the determination of S. aureus nasal carriage when comparing flocked swabs to rayon swabs; however, those authors used a different microbiological procedure than ours, consisting of an overnight preenrichment broth step, followed by plating on chromogenic agar. The latter process is known to improve the sensitivity of bacterial detection (3,10,13,15), but it is timeconsuming since the results are delayed by 1 day, which may be a determinant for the detection of nasal carriers when decontamination treatment must be applied to prevent S. aureus infection, for instance, just before a surgical procedure (4) or the arrival of the patient in an intensive care unit.…”
contrasting
confidence: 45%
See 2 more Smart Citations
“…Similarly, Van Horn et al have demonstrated that nylon flocked swabs placed in Amies liquid medium yielded greater organism release (18). In contrast to these results, a recent study from De Silva et al (8) did not find any difference in the determination of S. aureus nasal carriage when comparing flocked swabs to rayon swabs; however, those authors used a different microbiological procedure than ours, consisting of an overnight preenrichment broth step, followed by plating on chromogenic agar. The latter process is known to improve the sensitivity of bacterial detection (3,10,13,15), but it is timeconsuming since the results are delayed by 1 day, which may be a determinant for the detection of nasal carriers when decontamination treatment must be applied to prevent S. aureus infection, for instance, just before a surgical procedure (4) or the arrival of the patient in an intensive care unit.…”
contrasting
confidence: 45%
“…In comparison to the use of rayon swabs, the use of flocked swabs has been demonstrated to improve the uptake of epithelial cells and viruses (1,7), to release more microorganisms in vitro (18), and to enhance the molecular detection of Chlamydia trachomatis and Neisseria gonorrhoeae (6). Despite these apparent advantages, a recent study that compared flocked and rayon swabs after a 24-h broth culture enrichment did not show any difference in the rate detection of S. aureus nasal carriers (8). To further assess the utility of flocked swabs, we conducted a study similar to that mentioned just above, with the exception that no enrichment step was performed.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have demonstrated the superior absorption and releasing capacity of ESwabs, in comparison with traditional swabs (13)(14)(15)(16)(17)(22)(23)(24). The ESwab is a revolutionary concept because of its ability to offer what standard swabs cannot provide; ESwabs elute the entire sample into 1 ml of transport medium, providing identical aliquots of liquid sample suspension, which enables laboratories to determine and to validate the optimal specimen volumes (and therefore analyte amounts) for use in their assays.…”
mentioning
confidence: 99%
“…rotavirus) the mean nucleic acid yield was actually higher with the traditional swabs, this would suggest that sequence of sample collection did not always disadvantage the second swab. Several paired swab studies of other mucosal surfaces have shown that sequence of swab collection did not significantly affect sensitivity for pathogen detection (18, 19). One possible reason that the flocked rectal swab outperformed the traditional swab for Shigella detection is that it has a “stopper” at 3.2cm mark and this might aid in ensuring adequate sampling at the rectal mucosa (where Shigella causes pathology).…”
mentioning
confidence: 99%